DEVELOPING QUR’AN-BASED MATHEMATICS TEACHING MATERIALS FOR 21ST-CENTURY LEARNING - Afni Dea Yunesti; Nurbaiti Widyasari (KALAMATIKA Jurnal Pendidikan Matematika, 2022)
This study aims to develop Qur’an-based teaching materials for teaching lines in Grade 4 for 21st-century learning. This research is a research and development (R&D) research using the ADDIE model, involving the stages of analysis, design, development, implementation, and evaluation. The subjects in this study were 4th-grade students in Bekasi, Indonesia. The data were analyzed descriptively, and percentages were used to represent the results. The results showed that 1) validation of material experts indicated 77% with valid criteria, 2) validation of linguists reporting 87.5% with very valid criteria, and 3) validation of media experts resulting in 83% with very valid criteria. The assessment of students' responses revealed that a one-to-one trial with five subjects each showed an average of 95% with high criteria. Based on the results of this assessment, the Qur'an-based mathematics teaching materials for the topic of lines aligning to 21st-century learning are valid or suitable for use.